Bionanocomposite materials for electroanalytical applications: current status and future challenges - Deffo, Gullit; Tonleu Temgoua, Ranil Clément; Njanja, Evangéline; Puzari, Panchanan (Nanoscale advances, 2024)
Bionanocomposites are materials composed of particles with at least one dimension in the range of 1-100 nm and a constituent of biological origin or biopolymers. They are the subject of current research interest as they provide exciting platforms and act as an interface between materials science, biology, and nanotechnology and find applications in disciplines such as electrochemistry, biomedicine, biosorption, aerospace, tissue engineering and packaging. They have different properties such as high conductivity, thermal stability, electrocatalytic ability, biocompatibility, adsorption ability and biodegradability, which can be tuned by their preparation methods, functionalities and applications. However, depending on the objective or the goal of a research project, specific preparation and characterization of bionanocomposites can be undertaken to understand the behavior and confirm the applicability of a bionanocomposite in a given field. Like in electroanalysis applications, electrode materials should be porous (meso- and macro-porosities), having large specific area (at least having a Brunauer-Emmett-Teller surface of 200 m 2 g −1 ), higher stability over time with acceptable power recovery between 95% and 105%, good electrocatalytic ability, and be a good absorbent and a good conductor of electricity (that is to say, it facilitates the transfer of electrons from the solution to the surface of the electrode and vice versa ). The present review focuses on the most used method of preparation of bionanocomposites with the critical aspect and their physicochemical and electrochemical characterization techniques, and finally, the practical situations of application of bionanocomposite materials as modified electrodes for electroanalysis of several groups of analytes and a comparison with non-bionanocomposite electrodes are discussed. The future scope of bionanocomposites in the field of electroanalysis is also addressed in this review. But before that, a general overview of bionanocomposite materials in relation to other types of materials is presented to avoid any misunderstanding. Bionanocomposites are materials composed of particles with at least one dimension in the range of 1-100 nm and a constituent of biological origin or biopolymers.